A Case Study of a Writer Using Code Switching - Yayu Heryatun (Journal of English Language and Culture, 2017)
This research is intended to find out the types of code switching that is used in short stories and to describe the reasons why a writer does code switching in her short stories. It is a case study involving a writer of short story. Three short stories as document analysis and interview served as the data collection method. The result of this research indicated that the intra-sentential type of code switching occurs mostly in her short stories, followed by inter-sentential code switching. In addition, the reasons why code switching occurs are firstly, that certain notions or concepts are simply better expressed in the other language; secondly, code switching is used as a communicative or social strategy to show speaker involvement, mark group identity, exclude someone, raise one’s status, show expertise, and so on; thirdly, it is used to refill a linguistic need for a word or an expression; and finally, the last reason is to strengthen command. Keywords: Code switching, short stories